Information Literacy Skills Assessment in Digital Crisis Management Training for the Safety Domain: Developing an Unobtrusive Method - Steinrücke, Johannes; Veldkamp, Bernard P.; de Jong, Ton (Frontiers in Education, 2020)
This study aims to develop an unobtrusive assessment method for information literacy in the context of crisis management decision making in a digital serious game. The goal is to only employ in-game indicators to assess the players’ skill level on different facets of information literacy. In crisis management decision making it is crucial to combine an intuitive approach to decision making, build up by experience, with an analytical approach to decision making, taking into account contextual information about the crisis situation. Situations like these have to be trained frequently, for example by using serious games. Adaptivity can improve the effectiveness and efficiency of serious games. Unobtrusive assessment can enable game developers to make the game adapt to the players current skill level without breaking the flow of gameplay. Participants played a gameplay scenario in the Dilemma Game. Additionally, participants completed a questionnaire that was used as a validation measure for the in-game information literacy assessment. Using latent profile analyses, unobtrusive assessment models could be identified, most of which correlate significantly to the validation measure scores. Although inconsistencies in correlations between the information literacy standards, which call for broader testing of the identified unobtrusive assessment models, have been observed, the results display a good starting point for an unobtrusive assessment method and a first step in the development of an adaptive serious game for information literacy in crisis management decision making.